KONSEP WILÂYAH AL-FAQÎH DALAM SISTEM POLITIK SYI`AH IMAMIYAH - Lukpinius Lukpinius (Manthiq, 2016)
Abstract: The Concept Ofwilayatal-Faqih In The System Of Shia Imami. This article discusses the concept of wilayatal-Faqih in the system  of Shia Imamia and  its implementation in the state  leadership. Research type used  is library research and the method used  in this research is qualitative descriptive. From the results of this study found that in view of the Shi’a Imami, there is a strong link between the concept of Imamat and Wilayatal- Faqih concept. Both are the successor to the prophetic mission of religion in order to preserve and manage the affairs of the world. If the imam  is obliged  to guide people after the end of the “cycle of revelation,”  meaning after the death of the Prophet, then the duty of faqih is to guide people after the end of “Imamate cycle”. The differences between Imam  and al-faqih are; if the imam  are Ma’shum (avoid from sin), while the faqih does not ma’shum or have other  special  attributes similar to those  of the Imam.  But Al-Faqih has a position  in the state  if the executive and  judicial powers are in Wilayatal-faqih  who  perform  the function  as representative of the imam,  the legislative power  belongs  fully to God. Therefore,  governments in the wilayatAl-Faqih also be referred to as “the law of God’s rule over man”.  Parliament is required to draw  up programs for various ministries based on the teachings of Islam and determine the form of government services  across  the country. Thus, in the system of Wilayahal-Faqih, the scholars of al-faqih has a position, both as the guardian, interpreter and executor of the laws of God.